IMPLEMENTASI KEBIJAKAN OPERASI YUSTISI PROTOKOL KESEHATAN DI KABUPATEN SIDOARJO - Arthemevia Indhawati; Putra Riyan Izzuddin; Muhammad Aulia Yahya; Susi Hardjati (Universitas Halu Oleo, 2021)
Government held Operation Yustisi, so the public could be more aware of the importance of keeping distance to prevent spread of COVID-19 which was increasingly widespread. This study describe the effectiveness of the Yustisi Operation to public in order to increase public awareness, suppress spread of the COVID-19 outbreak in Sidoarjo. This study uses descriptive qualitative approach. Using Indicators of success of public policy implementation are seen from four factors as stated in the policy implementation model from Edward III. At the time of the Justisi operation, the officers are expected to able convey in a professional manner and run public services to have good communication. Obstacle in the Justisi Operation that was conveyed was that the community had not obeyed the rules and ignore health protocols because it was necessary to carry mask surgery and medical protocol operation regularly as often as possible.